2010
DOI: 10.1111/j.1526-100x.2008.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community Recovery following Restoration in Temporally Variable Riparian Wetlands

Abstract: Wetlands historically provided many ecosystem services but most have been lost or degraded through land conversion. Recent appreciation for wetland values and increasing ecotourism in the Central Platte River Valley (U.S.A.) has promoted restoration of wet meadow systems, although recovery patterns are not well known. We quantified plant community structure in sloughs (deeper habitats) and adjacent margins (slightly higher elevation) of six wetland sites, restored for 1-7 years at the onset of a 3-year study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 55 publications
(60 reference statements)
1
28
0
1
Order By: Relevance
“…For example, even after 39 years, Lennox et al (2011) observed no response of perennial herbaceous species to restoration of riparian woody vegetation. However, the literature also includes cases when riparian vegetation showed rapid recovery, for instance, after elimination of grazing (Hough-Snee et al 2013) or alien clearing (Ruwanza et al 2013), as well as examples of intermediate recovery rates (Meyer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, even after 39 years, Lennox et al (2011) observed no response of perennial herbaceous species to restoration of riparian woody vegetation. However, the literature also includes cases when riparian vegetation showed rapid recovery, for instance, after elimination of grazing (Hough-Snee et al 2013) or alien clearing (Ruwanza et al 2013), as well as examples of intermediate recovery rates (Meyer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mesic grass and sedge complexes with meandering linear sloughs in low-lying areas. Substrata within these sloughs are predominantly sand and silt, and vegetation cover ranges from 0 to 100% (Meyer et al , 2010. Sloughs in this region range from ephemeral to perennial, depending on evapotranspiration, precipitation, and groundwater connections to Platte River channels (Wesche et al 1994;Whiles and Goldowitz 1998).…”
Section: Study Regionmentioning
confidence: 98%
“…The length of time since transplantation (Heleno et al 2010), and the timing of the restoration event (Fegley et al 2009) relative to reproduction recruitment and important environmental factors (e.g. rainfall, temperature; Cummings et al 2007, Meyer et al 2010 may also be important.…”
Section: Discussionmentioning
confidence: 99%